Human health in systemic adaptation to climate change: insights from flood risk management in a river basin - Timo Assmuth; Tanja Dubrovin; Jari Lyytimäki (Environment Systems and Decisions, 2020)
Human health risks in dealing with floods in a river basin in South-Western Finland are analysed as an example of scientific and practical challenges in systemic adaptation to climate change and in integrated governance of water resources. The analysis is based on case reports and plans, on literature studies and on conceptual models of risks and risk management. Flood risks in the Northern European study area are aggravated by melt- and storm-water runoff, ice jams and coastal flooding. Flood risk assessment is linked with management plans based on EU directives as applied in the case area. National risk management policies and procedures of increasing scope and depth have been devised for climate change, water resources and overall safety, but an integrated approach to health risks is still largely missing. The same is true of surveys of perceived flood risks, and participatory deliberation and collaborative planning procedures for flood risk management in the case area, specifically for adaptive lake regulation. Health impacts, risks and benefits, socio-economic and systemic risks, and over-arching prevention, adaptation and compensation measures are not fully included. We propose a systematic framework for these extensions. Particular attention needs to be given to health risks due to flooding, e.g. from water contamination, moist buildings, mental stress and infrastructure damage and also from management actions. Uncertainties and ambiguities about risks present continuing challenges. It is concluded that health aspects of flooding are complex and need to be better included in assessment and control, to develop more integrated and adaptive systemic risk governance.

Integrative concepts and practices of health in transdisciplinary social ecology - Timo Assmuth; Xianwen Chen; Christopher Degeling; Tari Haahtela; Katherine N. Irvine; Hans Keune; Richard Kock; Salla Rantala; Simon Rüegg; Suvi Vikström (Socio-Ecological Practice Research, 2020)
Increasing recognition of interdependencies of the health of humans, other organisms and ecosystems, and of their importance to socio-ecological systems, necessitates application of integrative concepts such as One Health and EcoHealth. These concepts open new perspectives for research and practice but also generate confusion and divergent opinion, prompting new theories, and call for empirical clarification and evaluation. Through a semi-systematic evaluation of knowledge generation in scientific publications (comprised of literature reviews, conceptual models and analyses of communities of practice), we show how integrative concepts and approaches to health evolve and are adopted. Our findings indicate that while their contexts, goals and rationales vary, integrative concepts of health essentially arise from shared interests in living systems. Despite recent increased attention to ecological and societal aspects of health including broader sustainability issues, the focus remains anthropocentric and oriented towards biomedicine. Practices reflect and in turn transform these concepts, which together with practices also influence ways of integration. Overarching narratives vary between optimism and pessimism towards integrated health and knowledge. We conclude that there is an urgent need for better, coherent and more deeply integrative health concepts, approaches and practices to foster the well-being of humans, other animals and ecosystems. Consideration of these concepts and practices has methodological and political importance, as it will transform thinking and action on both society and nature and specifically can enrich science and practice, expanding their scope and linking them better. Transdisciplinary efforts are crucial to developing such concepts and practices to properly address the multiple facets of health and to achieve their appropriate integration for the socio-ecological systems at stake. We propose the term “transdisciplinary health” to denote the new approaches needed.

The good, the bad and the ugly: framing debates on nature in a One Health community - Nicolas Antoine-Moussiaux; Luc Janssens de Bisthoven; Stéphane Leyens; Timo Assmuth; Hans Keune; Zinsstag Jakob; Jean Hugé; Maarten P. M. Vanhove (Sustainability Science, 2019)

Presence of active pharmaceutical ingredients in the continuum of surface and ground water used in drinking water production - Heidi Ahkola; Sirkku Tuominen; Sanja Karlsson; Noora Perkola; Timo Huttula; Sami Saraperä; Aki Artimo; Taina Korpiharju; Lauri Äystö; Päivi Fjäder; Timo Assmuth; Kirsi Rosendahl; et al. (Environmental Science and Pollution Research, 2017)

Policy and Science Implications of the Framing and Qualities of Uncertainty in Risks: Toxic and Beneficial Fish from the Baltic Sea - Timo Assmuth (Ambio, 2011)